Evaluating the Liming Potential of Mytilus galloprovincialis Shell Waste on Acidic Soils - Alexios Lolas; Katerina Molla; Konstantinos Georgiou; Chrysoula Apostologamvrou; Alexandra Petrotou; Konstantinos Skordas; Dimitris Vafidis (Conservation)
The sustainable management of aquaculture by-products is crucial for advancing circular economy practices. Mediterranean mussel shell waste, rich in calcium carbonate, presents a sustainable alternative to conventional liming materials, especially for mitigating soil acidification, a very important and common issue that limits crop productivity. This study evaluated the effectiveness of processed mussel shell waste in enhancing soil pH, organic matter, and nutrient availability. A 180-day pot experiment using highly acidic soil (pH < 4.5) collected from a local field was conducted in a Completely Randomized Design. Treatments involved two grain sizes of mussel shell powder (Fine: <1 mm; Coarse: 1–2 mm) at rates between 0.1 and 6%. Treated soil pH was measured monthly, whereas organic matter, available phosphorus (P), and exchangeable potassium (K) were measured at the beginning and the end of the experiment. The results revealed significant improvements in pH, organic matter, available phosphorus (P), and exchangeable potassium (K), particularly in the Fine Powder treatments. However, total nitrogen (N) remained unaffected. These findings highlight the potential of mussel shells as an eco-friendly and cost-effective amendment, advancing sustainable agriculture and waste recycling, thus contributing to broader conservation efforts by reducing the environmental footprint of aquaculture waste and supporting biodiversity and ecosystem resilience through sustainable resource management.